Investigating the “queen bee” phenomenon in Indonesia: a case study - S Suharnomo; Devita Permatasari (Diponegoro International Journal of Business, 2019)
The purpose of this research was to explore the experience of some informants regarding the phenomenon of queen bee in Indonesia. Our study used qualitative method with case study approach. Data was gathered using in-depth interview on seven informants. The result shows that the queen bee leader did intimidating and mostly not supporting the career of her subordinate woman. Besides, the queen bee leader make distance not only to her subordinate which are female, but also to her female colleagues at work. Queen bee leader tend to give preferential treatment to men. This phenomenon has more negative impacts than positive impacts. The negative impact caused by the queen bee phenomenon is that it can cause victim to be feel intimidatied and stressed, the work atmosphere becomes less conducive, uncomfortable, disrupts the operations of the company. While the positive impact of the existence of the queen bee leader is the job need to be due became quicker to be completed.